Muslim attitude towards participation in cash WAQF: Antecedents and consequences - Shukor S.A.; Anwar I.F.; Shukor S.A.; Sabri H. (Universiti Malaysia Sarawak, 2024)
Waqf creates great benefits not only for the endower but also for the whole society. Endowment of waqf is generally known in terms of porperty but little attention given to endowment of cash waqf. This paper aims to investigate antecedents and consequences of Muslim attitude towards participation in cash waqf in Malaysia. The findings of this paper are based on 386 samples. Descriptive analysis, exploratory factor analysis and regression analysis are used to analyse the data. The results indicate that individual religiosity, trust in awqaf institutions and convenience to endow are antecedents of Muslim attitude towards participation in cash waqf, which consequently leads to individual intention to participate in the practice. The study provides a useful source of information to related parties for instance the waqf institution and Islamic regulatory body in executing effective startegy to promote cash waqf as well as reinforcement of systematic collection procedures that can benefit the community. 2017, Universiti Malaysia Sarawak. All rights reserved.